(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of second-line Docetaxel monotherapy in patients with esophageal squamous cell carcinoma at Nghe An Oncology Hospital. Subjects and methods: A retrospective descriptive study was conducted on 61 patients with esophageal squamous cell carcinoma who received second-line Docetaxel monotherapy between January 2023 and December 2025 at Nghe An Oncology Hospital. Results: The mean age of the patients was 59.79 ± 6.7 years. The proportion of patients completing six cycles of chemotherapy was 45.9%. The disease control rate was 49.2%, with a partial response rate of 32.8%. Tumor T stage, overall disease stage, number of metastatic organs, and sites of metastasis were significantly associated with treatment response (p < 0.05). The most common hematologic toxicity was neutropenia, with grade 3-4 neutropenia occurring in 14.8% of patients; febrile neutropenia was observed in 8.2% of patients. Other adverse events were predominantly grade 1-2. Conclusion: Second-line Docetaxel monotherapy demonstrated favorable efficacy and an acceptable safety profile in patients with esophageal squamous cell carcinoma who experienced disease progression following first-line treatment.